Intimate partner violence among women with HIV infection in rural Uganda: critical implications for policy and practice - Osinde Michael O; Kaye Dan K; Kakaire Othman (BMC, 2011)
Abstract Background Intimate partner violence (IPV) is a major public health problem in Africa and worldwide. HIV infected women face increased IPV risk. We assessed the prevalence and factors associated with IPV among HIV infected women attending HIV care in Kabale hospital, Uganda. Methods This cross-sectional study was conducted among 317 HIV infected women attending Kabale regional hospital HIV treatment centre, from March to December 2010. Participants were interviewed using an interviewer-administered questionnaire. Data was collected on socio-demographic variables, social habits, and IPV (using the abuse assessment screen and the Severity of Violence against Women Scale to identify physical, sexual and psychological violence). Characteristics of the participants who reported IPV were compared with those who did not. Multivariate logistic-regression analysis was conducted to analyze factors that were independently associated with IPV. Results The mean age of 317 respondents was 29.7 years. Twenty two (6.9%) were adolescents and 233 (73.5%) were married or cohabiting. The mean age of the spouse was 33.0 years. One hundred and eleven (35.0%) were currently on antiretroviral therapy. Lifetime prevalence of IPV (physical or sexual) was 36.6%. In the preceding 12 months, IPV (any type) was reported by 93 respondents (29.3%). This was physical for 55 (17.6%), and sexual /psychological for 38 (12.1%). On multivariate multinomial logistic regression analysis, there was a significant but inverse association between education level and physical partner violence (adjusted relative risk (ARR) 0.50, confidence limits (95% CI) 0.31-0.82, p-value = 0.007). There was a significant but inverse association between education level of respondent and sexual/psychological violence (ARR 0.47 95%CI (0.25-0.87), p-value = 0.017) Likewise, there was a significant inverse association between the education level of the spouse and psychological/sexual violence (ARR 0.57, 95% CI 0.25-0.90, p-value = 0.018). Use of antiretroviral therapy was associated with increased prevalence of any type of violence (physical, sexual or psychological) with ARR 3.04 (95%CI 1.15-8.45, p-value = 0.032). Conclusion Almost one in three women living with HIV had suffered intimate partner violence in the preceding 12 months. Nearly one in five HIV patients reported physical violence, and about one in every seven HIV patients reported sexual/psychological violence. Likewise, women who were taking antiretroviral drugs for HIV treatment were more likely to report any type of intimate partner violence (physical, sexual or psychological). The implication of these findings is that women living with HIV especially those on antiretroviral drugs should be routinely screened for intimate partner violence.